Development Of An Android-Based Multimedia E-Book To Enhance Collaboration Skills Of Elementary School Students - Tri Sutrisno; Solehan, Samar (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to develop an Android-based multimedia e-book that is valid, practical, and effective in enhancing the collaboration skills of elementary school students. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, and Disseminate). The participants were 32 fifth-grade students at State Elementary School Cangkreng, Lenteng District, Sumenep Regency. Data were collected through expert validation sheets, implementation observations, student response questionnaires, and pretest–posttest collaboration skill assessments. The validation results indicated that the e-book achieved a highly feasible level of validity, with the average score increasing from 3.53 to 4.69 after revisions. The product also demonstrated high practicality, with an average score of 88.25% on implementation observations and 90.5% on student responses. The e-book’s effectiveness was evidenced by an increase in the average collaboration skill score from 67.31 to 85.06 and an improvement in learning mastery from 31.25% to 93.75%. A paired t-test revealed a t-value (12.84) greater than the critical t-table value (2.04), indicating a significant improvement after using the e-book. Therefore, the developed Android-based multimedia e-book is feasible for use as an innovative learning medium to enhance students’ collaboration skills, while also supporting the implementation of the Merdeka Curriculum and strengthening the Pancasila Student Profile